Hierarchical faulted line section location method for low‐voltage active distribution network considering information distortion. (21st August 2020) - Le, Jian; Zhao, Liangang; Xu, Fengqian; Zheng, Zhixiang; Wang, Qizhe
Abstract: Distortion of fault monitoring information is an important factor that affects the accuracy of faulted line section location in low‐voltage active distribution networks (ADNs). This paper proposes a faulted line section location method that considers the layered solution for monitoring information distortion, to improve the accuracy and efficiency of fault location in low‐voltage ADNs. A multi‐target fault section location optimization model that considers information distortion, multipoint faults, and multiple information distortion types is formulated. A combination of information distortion factors is introduced to represent various types of information distortion and to transform the original optimization model into an unconstrained 0‐1 programming problem. A hierarchical fault location algorithm for segmenting the distribution network is designed to solve the low accuracy and efficiency of direct solutions for fault location models resulting from a large number of active distribution line sections. Simulation results show that the fault location method considering information distortion effectively guarantees the accuracy and solution efficiency of faulted line section location of low‐voltage ADN. Abstract : The monitoring devices upload the fault current information and active distribution network topology information to the database. The server optimizes the topology structure according to the hierarchical equivalent principle, a combination of information distortion factors is introduced to represent various types of information distortion, and finds the fault section using the BPSO fault location algorithm.